Real-time hand tracking and gesture analysis for virtual rehabilitation monitoring system - Zainuddin, Ahmad Anwar; Basri, Atikah Balqis; Badrulhisham, Nurul Iffah; Zulkifli, Nurul Nabilah; Mohd Abu Bakar, Nur Athirah; Nik Mohd Kamal, Nik Nor Muhammad Saifudin; Ahmad Puzi, Asmarani; Kaitane, Wonderful Shammah; Johar, Mohd Naqiuddin (Universiti Teknologi MARA (UiTM) Cawangan Pahang, 2023)
The field of computer vision has experienced notable progress and presents advantageous implementations across diverse sectors, such as the healthcare industry. The domain of rehabilitation is a prime example of an area where the utilization of this technology is greatly coveted. At present, individuals undergoing rehabilitation are mandated to make frequent visits to medical facilities for the purpose of monitoring their physical advancement, with a particular emphasis on hand stretching exercises. Nonetheless, this procedure is frequently inconvenient and time-consuming as a result of the necessity for frequent travel. In order to tackle this matter, we suggest the implementation of a computer vision-based virtual rehabilitation monitoring system. The system utilizes a webcam that is linked to a computer and a Python software to facilitate the remote observation of hand stretching exercises. This methodology obviates the necessity for patients to commute to medical facilities for rehabilitation sessions, thereby facilitating them to conveniently execute their exercises in the comfort of their own homes. The underlying technique utilized by the system is the Multimedia Development Life Cycle (MDLC). In order to achieve maximum precision, the patient is required to establish a connection with a webcam, initiate the software, and extend their palm to a distance of approximately 30 centimeters from the camera. Extensive testing was carried out on the system, revealing its efficacy in real-time hand point detection and volume calculation through hand stretching. This work addresses the challenges related to hospital-based rehabilitation by offering patients a convenient and stress-free rehabilitation experience, thereby overcoming travel barriers.